Genetic and environmental effects affecting the variation in birth date and birth weight of reindeer calves - Muuttoranta, Kirsi; Holand, Øystein; Røed, Knut H.; Tapio, Miika; Nieminen, Mauri; Mäki-Tanila, Asko (Rangifer, 2013)
The factors causing variation in birth date and birth weight were analysed from the data from an experimental reindeer herd consisting of 1136 calves with parental information. The traits had coefficient of variation of 37 and 14%, respectively. The variation in both traits was affected by year and sex (male calves heavier) and by management factors, such as the age distribution of females and males. Early calving results from the use of older breeding males and is most apparent in prime age females. In both traits the heritability was moderate (0.23 and 0.24) with a high proportion of maternal genetic variation (0.23) in birth weight. The North Atlantic Oscillation (NAO) indices, summarizing the major weather conditions prior to rut, explained part of the annual variation in the traits. The amount of total genetic variation in relation to trait mean, or the evolvability, was 21% in birth date and 10% in birth weight indicating that selection could successfully be used to improve herd productivity and that the traits have substantial potential for adapting to possible changing environmental conditions. The results on genetic correlations imply that selection on calf’s birth weight leads on one hand to calves being born earlier and on the other hand to dams with later parturition.
Keywords: birth weight; birth date; genetic correlation; heritability; maternal effect; Rangifer tarandus; reindeer